ELECTROMAGNETIC COUPLING TO A NONUNIFORM TRANSMISSION-LINE CONSISTING OF 2 ANGLED WIRES - HONG, SY; RA, JW; KIM, SY (JOHN WILEY & SONS INC, 1992)
A new method is developed to analyze electromagnetic coupling to an angled two-wire transmission line. It consists of solving the cylindrical transmission line equations analytically, and then adjusting the involved parameters to support the cylindrical TEM mode along its equivalent model of the angled two-plate transmission line. The validity of the derived solution is assured by showing its convergence to the numerical value obtained by using the circuit concept approach.